PENGARUH KESADARAN MERK DAN PERSEPSI KUALITAS TERHADAP KEPUTUSAN PEMAKAIAN JASA PENERBANGAN GARUDA INDONESIA : (Rute Keberangkatan Dari Pontianak) - Syifa Fauziah; Wahyu Istigh Fadila Daraja (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine the effect of brand awareness and perceived quality and to find out the attributes of brand awareness and perceived quality on the Garuda Indonesia airline on the departure route from Pontianak at Supadio Pontianak Airport which needs to be developed. This research was conducted for one month, using three dimensions of service usage decisions, namely Confidence in using services, Stability in using services, Conformity of attributes to needs and desires. The sample of this research is Garuda Indonesia airline passengers. The sample for this research used purposive sampling method. Data were collected using questionnaires and literature studies. The research method uses a quantitative research design in the form of a survey with classical assumption tests, multiple regression analysis and hypothesis testing. The results of this study show that the data is normally distributed with a significance level of 0.150 or > 0.05 and shows a unidirectional relationship between the independent variable and the dependent variable. It can be concluded that Garuda Indonesia airline passengers at Supadio Pontianak airport were satisfied with the brand and quality provided with a value (51.9%). Each variable dimension can be developed in order to increase brand awareness and perceived quality in this study.